(untitled) (Research, Society and Development, 2021)
The main objective of this study is: to increase knowledge about molding techniques in open and closed trays. As secondary objectives, it is proposed: to study about implant prostheses; characterize the distinctions between open and closed trays; expand knowledge about the most suitable situations for the use of each tray style (open or closed). The present study is a descriptive and qualitative bibliographic survey, using theoretical references extracted from books, scientific articles, monographs, theses, revised dissertations and electronic websites that portray the proposed theme. In recent years, the demand for the rehabilitation of tooth loss with implants has become popular. In the current stage of development that implant prostheses have reached, they are considered to be the best treatment options, being considered as a high standard within dental prostheses. The main objective of an implant prosthesis molding is to accurately record the positioning of the components in the mouth and soft tissues, as well as the structures adjacent to the edentulous space, thus using specific components for transfer, as well as metallic analogues of the present device. in the mouth, whether abutments or implants. Among the molding techniques we have the technique with open tray and with closed tray. Therefore, the choice between open or closed tray will be based on the characteristics of the components and rehabilitation that will be carried out. Both techniques have their advantages, however, each is indicated for specific cases. In this sense, the choice will be based on the individual demand of each patient.